PENGOLAHAN PRODUK ANTI STUNTING MASYARAKAT DESA SUMODIKARAN KECAMATAN DANDER KABUPATEN BOJONEGORO - Tsaqibul Fikri; Fakhrun Nisa; M. Jauharul Maarif (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2023)
One of the problems being faced by the people of Sumodikaran Village is the problem of chronic nutrition or stunting, where there are at least 3 children experiencing stunting and 3 children experiencing malnutrition in the village. Possible factors for this to occur include the low quality of micronutrients in food, low intake of a variety of foods from animal sources, and giving children additional food that is low in energy. However, on the other hand, society is also hampered by the low economy so that it is unable to provide better nutritional intake for children. The lack of knowledge of village communities regarding marketing strategies is one of the problems that has an impact on the village economy. The aim of implementing this Community Service is to reduce chronic or stunting nutrition in Sumodikaran village. This service is carried out using a systematic method with 2 stages, namely preparation and implementation. Where the implementation consists of 3 steps such as socialization on stunting prevention, socialization on digital marketing and introduction to graphic design and preparation of materials and processing of anti-stunting products. The results of this community service are in the form of increasing public understanding and knowledge about the importance of reducing malnutrition or stunting by improving the economy through processing nutritious snacks and at the same time marketing them